Effect of cavity preparation instruments (oscillating or rotating) on the composite-dentin interface in primary teeth - Pioch, Thomas; Garcı́a-Godoy, Franklin; Duschner, Heinz; Koch, Martin Jean; Staehle, Hans Jörg; Dörfer, Christof (Dental materials, 2003)
To evaluate the effect of preparation of instruments on the interfacial integrity between cavity wall and composite restoration.
Available online 22 March 2002
Gesehen am 17.02.2021